Keterampilan Berpikir Kritis Dan Penguasaan Konsep Siswa Melalui Pembelajaran RADEC Menggunakan Media Zoom Meeting Pada Materi Perubahan Wujud Benda Kelas V - Heryanti, Feny Rosa; Sujana, Atep; Saputra, Yudha Munajat (Jurnal Pena Ilmiah, 2021)
Critical thinking and mastery of important concepts are owned by students in the 21st century, but in the field the condition of students in critical thinking and mastery of concepts still looks low. RADEC learning is a new breakthrough in education in order to achieve the competencies possessed by students in the 21st century. This research is a qualitative descriptive study. The purpose of this study is to find out how the implementation of RADEC learning is, how critical thinking skills and mastery of concepts are for class V students on Material Changes in Objects through RADEC learning using Zoom Meeting. The subjects in this study were fifth grade students at SDN Sukamantri, Paseh District, Bandung Regency. The instruments used are observation and tests. The conclusion of this research is that through the RADEC learning model students are able to think critically and master the concept and mastery of the RADEC model is effective and suitable to be applied in learning so as to make learning more meaningful even though it is carried out online.